IMPLEMENTASI KONSEP MULTIPLE INTELLIGENCES DALAM PEMBELAJARAN QUR’AN HADIS DI MAS MADANI ALAUDDIN, GOWA, SULAWESI SELATAN - Syarifah Huriyah; Erwin Hafid; Muhammad Rusdi (Jurnal Tarbiyah Almuslim, 2024)
The main problem of this research is how the concept of multiple intelligences is used in Qur'an hadith learning at MAS Madani Alauddin, Gowa, South Sulawesi. The main problem is then included in several sub-problems or research questions: How is the planning, implementation and assessment of Qur'an hadith learning at MAS Madani Alauddin, Gowa, South Sulawesi. This type of research is classified as qualitative with the research approaches used being phenomenology. The data sources for this research were the Qur'an hadith subject teacher and two class X students. The data collection methods used were observation, interviews and documentation. Meanwhile, data processing and analysis techniques are carried out through three stages: data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation of the concept of multiple intelligences in learning the Qur'an hadith at MAS Madani Alauddin, Gowa, South Sulawesi, which includes planning, implementation and evaluation, has only just begun to be implemented as a support for differentiated learning in the independent curriculum and is still being implemented. requires a lot of evaluation to perfect the learning process. However, learning with the concept of multiple intelligences is more optimal if applied to learning outside mandatory class hours.